2012
DOI: 10.1002/bjs.8677
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of outcomes after intersphincteric resection for low rectal cancer

Abstract: Oncological outcomes after ISR for low rectal cancer are acceptable, with diverse, often imperfect functional results. These data will aid the clinician when counselling patients considering an ISR for management of low rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
151
1
23

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(192 citation statements)
references
References 63 publications
17
151
1
23
Order By: Relevance
“…26 Recently, a review of 14 high quality reports including over 1,200 patients was published. 27 An R 0 resection was achieved in 97 % of patients with an average DRM of 1.7 cm and a negative CRM in 96 %. Mean oncologic outcomes were similar to initial reports but ranges varied widely.…”
Section: Intersphincteric Resectionmentioning
confidence: 90%
See 1 more Smart Citation
“…26 Recently, a review of 14 high quality reports including over 1,200 patients was published. 27 An R 0 resection was achieved in 97 % of patients with an average DRM of 1.7 cm and a negative CRM in 96 %. Mean oncologic outcomes were similar to initial reports but ranges varied widely.…”
Section: Intersphincteric Resectionmentioning
confidence: 90%
“…28 Lack of a standardized assessment instrument and inconsistent reporting of functional outcomes in recent, larger series make consensus on functional outcome after ISR difficult. In a review of eight studies reporting outcomes, 11-63 % of patients reported fecal soiling and 30-86 % reported perfect continence 27 with statistical assessment of the data showing wide confidence intervals. The most likely interpretation of the results is that functional outcome after ISR is highly variable.…”
Section: Intersphincteric Resectionmentioning
confidence: 99%
“…Los pacientes sometidos a una resección abdominoperineal (RAP) tienen una tasa de RL mayor que la resección anterior baja, lo que probablemente refleja un sesgo de selección 10 . El riesgo de RL de la resección interesfintérica en tumores muy bajos es en la actualidad motivo de discusión 11 . En el extremo del abanico, los pacientes con una RL luego de resección local, tienen un mejor pronóstico relativo y mayor posibilidad de lograr una resección R0.…”
Section: Evaluación Preoperatoria De La Rlunclassified
“…This procedure proceeds in the left lower quadrant abdominal colostomy patients with a permanent colostomy, and cannot easily accept. In 1992 Braun et al [1].first reported by resection of internal sphincter (intersphincteric resection,ISR) in the treatment of tumor position of Ultralow rectal cancer of the anal 5cm in 2012 Ireland by doctor Martin [2]. System reviews the 14 units were reported, 1289 admits patients with intersphincteric resection for low rectal cancer information, where resection rate(RO) of 97%, operative mortality is 0.8%, 5-year survival rate is an average of 86.3%, 5-year disease-free survival rate was 78.6%, anal function full scale is 51.2%.…”
Section: Introductionmentioning
confidence: 99%